Daily field checking list by Walter Rosene, May 15, 1934 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated May 15, 1934. This checklist was used by Walter Rosene to record birds sighted around Beaver Bayou between 6:00 and 8:00. Plustek--flatbed